Kontribusi Regulasi Emosi terhadap Suicide Ideation pada Dewasa Awal di Sumatera Barat - Anastia, Shabrina Poetry; Ningsih, Yuninda Tria (YASIN, 2025)
This study was conducted with the aim of seeing the contribution of emotional regulation to suicide ideation in early adulthood in West Sumatra. This study used an accidental sampling technique with 400 early adult respondents in West Sumatra who had had suicidal thoughts. This study used the revised-suicide ideation scale (R-SIS) and emotion regulation questionnaire (ERQ). The results of the study showed a contribution of emotional regulation to suicide ideation in early adulthood in West Sumatra, emotional regulation contributed 85,4% to suicide ideation.